- دور الابداع في اثراء العمل الإداري لاكتساب الميزة التنافسية في المؤسسات - Bouchikhi, Mouhamed rida; Mohamed, Yagoub; Ghrissi, Sadouki (Finance and Business Economies Review, 2018)
The aim of this study is to see the impact of administrative innovation in building competitive advantage in SME, through empirical study on a sample of SME in Mascara, where the highlight was the interest and creativity of these institutions believe its importance in contributing to the achievement of competitive advantage. Where we met a lot of facts indicating a lack of interest all these institutions in administrative creativity. We also found that the levels of creativity in the research sample is weak and not unreliable in acquiring or maintaining the competitive advantage of small and medium-sized enterprises especially in light of developments in the Algerian economy